Hubungan Perilaku dalam Pemenuhan Kebutuhan Nutrisi dengan Derajat Hipertensi pada Pasien Hipertensi di Kelurahan Balai Gadang Wilayah Kerja Puskesmas Air Dingin - Bunga Fatihul Rahmi; Efitra Efitra; Wiwi Sartika; Murniati Muchtar; Yessi Fadriyanti (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
Hypertension is a health condition with an increase in blood pressure. As a result, you are at risk of experiencing other diseases such as stroke, heart disease and even death. One of the risk factors that can be changed is behavior. Behaviors that can increase blood pressure such as consuming foods high in salt and fat. The aim of this study was to determine the relationship between behavior in fulfilling nutritional needs and the degree of hypertension in hypertensive patients. This type of research was an analytic survey with a cross-sectional study design. This research was conducted in the Balai Gadang Sub-District, the Working Area of the Air Cold Health Center starting from January to June 2022. The study population was all hypertension patients who were in the Balai Gadang Sub-District. The research sample used the accidental sampling technique with the Lameshow formula as many as 53 people. Data collection used a questionnaire, processing with the stages of editing, coding, entry, cleaning.. Analysis was carried out using the Chi Square test frequency distribution (CI 95%). The results showed hypertension degree 1 (56.6%), high level of knowledge (54.7%), negative attitude (50.9%), action (58.5%) so that there is a relationship between behavior in fulfilling nutritional needs and the degree of hypertension, namely knowledge (p value = 0.006), attitude (p value = 0.000), and action (p value = 0.000). It is suggested to nurses to increase KIE education efforts about recommended foods in fulfilling nutritional needs to increase the knowledge of hypertensive patients in Balai Gadang Village.